Islamic-bank selection criteria in Malaysia: an AHP approach - Abduh, Muhamad; Omar, Mohd. Azmi (European Business School, Cambridge, UK, 2012)
The study of bank selection criteria has received attention from many bank marketing researchers. However, from its inception in three decades ago, this kind of study is still scanty for Islamic banking industry. The purpose of this study was to investigate the Islamic-bank selection criteria, particularly in Malaysia. To accomplish this purpose, information collected from 279 respondents within the Klang-valley area was incorporated in the analysis. The Analytic Hierarchy Process was used to rank the criteria based on the respondents’ preferences. The result has shown that shariah-compliant attribute is the highest priority before an individual decides to patronize an Islamic bank. The next priorities are given to profitability, bank’s reputation, bank’s status, facilities and services, and friendly personnel respectively. Thus, one of the implications of this study is that Islamic banks cannot be too liberal by following all the footprints of conventional bank without giving attention to shariah principles and objectives of shariah.